Aprovechamiento sostenible de residuos sólidos orgánicos para la generación de biogás en una finca ganadera de economía familiar en Timaná (Huila) (2020)
The present work is based on the evaluation of the best technology for the sustainable use of organic solid waste produced by heads of dairy cattle in a familyowned farm, for the generation of biogas through the implementation of a biodigester that is coupled with the characteristics of the farm. First, a review of the literature was developed to explain what a family economy farm is, the biodigestion process and what are the technologies available for the use of organic solid waste produced by dairy cattle. Subsequently, the quantification of the waste generated in the “El Chontaduro” farm was carried out, determining its characteristics, finding a production of 9 cubic meters of organic solid waste / Week. The available biodigester technologies in the literature and in the market were determined, finding biodigestors of fixed dome, floating dome, flexible structure, horizontal and Batch types, among others; selecting the first three to match the needs of the farm. Finally, a decision was made through the SuperDecisions software, implementing criteria such as construction, costs, durability and maintenance, visual impact and operating pressure, to determine the best technology to implement in the farm, predicting that the flexible structure digester It is the best alternative.